Menjadi Sahabat Sejati Teladan Kemartiran dari Santo Maximiliam Kolbe - Iswandir, Lorentius; Isharianto, Rafael (Forum, 2024)
Modern human life is characterized by the centrality of the individual. The negative effect is that human attitudes tend to be individualistic or egoistic, which can erode the solidarity and altruist spirit of people who want to be friends for others. Thus, the challenge to become a true friend is self-sacrifice. This paper aims to show as an example that there are still people who dare to sacrifice for others. From his spirit people can learn and take inspiration. This research intends to answer the question of whether there are still people in this modern world who can be used as examples of true friends. The author uses a historical approach and theological reflection, as well as a qualitative method of literature study. The results of this study show that being a friend is not a gift from birth, but a natural ability that can be cultivated and learned, as well as a supernatural power that can be invoked in commitment and spiritual fervor.